A Theoretical Analysis of Factors Influencing the Decision of Faculty to Use Educational Technologies in the Context of Institutions of Higher Education - Khan, Mohammad Ayub; Omrane, Amina; Rodríguez, Adriana Morales (Advances in Social Sciences Research Journal, 2017)
In this paper we study factors influencing faculty’s decision to use educational technologies to support their pedagogical strategies. We briefly describe educational technologies commonly used by faculty to support teaching such as emails, video conferences, chat rooms, video lectures, blackboard discussions and Power Point Presentations for example. We explain in detail faculty factors (i.e., gender, age and cultural background), student factors (i.e., academic performance and gender) and contextual factors (i.e., classroom size, institutional support, course subject, and time constraints) as influential factors in using educational technologies by the faculty to support teaching. The paper findings suggest that the factors under study do influence the faculty decision to use educational technologies to support teaching, however, there are certain strategies education institutions can rely upon in order to overcome the barriers that discourage the faculty to fully integrate technology into their pedagogical strategies.